2020
DOI: 10.22441/mix.2020.v10i1.006
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Entrepreneurial Marketing on Innovative Performance

Abstract: Resource Based Theory (RBT) is used to identify problems faced by SMEs. Based on the results of SWOT analysis, it can be seen that SMEs have six problems. These problems include: limited human resources, lack of advanced technology, not having enough knowledge about the target market, not having a good enough SMES management systems, competitor competition, and price from suppliers that fluctuate. The purpose of this study is to determine the effect of Entrepreneurial Marketing on Innovative Performance. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
1
0
3
Order By: Relevance
“…This proves that students have many ideas to create new advantages that still need to be created, but they are still unable to develop these ideas to become a business or old products to become new. Teofilus et al (2020) revealed that innovation is an understanding of entrepreneurship that is believed to provide a competitive advantage in the market that will be or is being faced. This is different from the results of research by (Iizuka et al, 2022), which found that taking risks positively and significantly influences the entrepreneurial intention of students in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…This proves that students have many ideas to create new advantages that still need to be created, but they are still unable to develop these ideas to become a business or old products to become new. Teofilus et al (2020) revealed that innovation is an understanding of entrepreneurship that is believed to provide a competitive advantage in the market that will be or is being faced. This is different from the results of research by (Iizuka et al, 2022), which found that taking risks positively and significantly influences the entrepreneurial intention of students in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Orientasi pasar dapat mempengaruhi keunggulan bersaing (Teofilus et al, 2020;Sismanto, 2020;Merakati et al, 2019;Lake et al, 2019;Sulistyo & Sri Ayuni, 2019;Herman et al, 2018Arifuddin, 2018Badruz, 2017;Merakati et al, 2017;Liliyani, 2015;Wachjuni, 2014;Patrional & Maria Magdalena, 2014;Vanessa, 2014;Sugiarti, 2013;Fatah, 2012;Gibran 2012). Oleh sebab itu hipotesis penelitian yaitu: H1: Terdapat pengaruh Orientasi Pasar terhadap Keunggulan bersaing pada Jasa Transportasi Berbasis Aplikasi Gojek Ukuran perilaku dan aktivitas yang mencerminkan praktik konsep pemasaran yang efektif dan efisien dalam orientasi pasar dapat meningkatkan kinerja pemasaran (Kohlil & Jawroski, 1990;Solyova, 2015).…”
Section: Hipotesis Penelitianunclassified
“…Dalam EO terdapat pemikiran proses pembuatan strategi yang dapat diwujudkan dalam kegiatan operasional suatu perusahaan yang memengaruhi keberhasilan wirausaha (Gupta dan Batra, 2016;Teofilus et al 2020). Keberhasilan wirausaha tergantung pada tindakan, komitmen, sikap, dan pengetahuan dalam memahami kualitas ketika praktik.…”
Section: Pendahuluanunclassified
“…EO dan TQM dapat dianggap sebagai sumber daya tidak berwujud yang bertujuan untuk membawa perusahaan berhasil dalam bersaing. Penerapan konsep TQM tidak akan berjalan dengan baik tanpa adanya penerapan EO pada setiap level dari manajemen perusahaan (Teofilus et al 2020). Hal itu menunjukkan bahwa EO dan TQM merupakan dua hal yang tidak dapat dipisahkan untuk membangun performa perusahaan yang stabil.…”
Section: Metode Penelitianunclassified